THE ROLE OF ORGANIZATIONAL COMMUNICATION IN REDUCING RESISTANCE TO CHANGE IN INDUSTRIAL COMPANIES IN INDONESIA - Bahdin Nur Tanjung; Melisa Nur Asima Sidabutar; Lusi Feriyami Sitompul (Mount Hope Economic Global Journal, 2025)
This study examines the role of organizational communication in reducing resistance to change in industrial companies in Indonesia. It is set against the background that industrial transformation is becoming increasingly intense—driven by the Fourth Industrial Revolution, sustainability demands, global competition, and regulatory changes—yet one of the main barriers is employees' resistance. Data indicates that about 65% of change programs experience moderate to high resistance, which results in implementation delays (average 40%), cost overruns (average 35%), and even complete failure (15% of cases). Resistance is treated as a multidimensional phenomenon influenced by cognitive, affective, and behavioral factors. The research uses mixed-methods with a sequential explanatory design: a quantitative phase involving 350 respondents from 35 companies and a qualitative phase involving 25 informants through in-depth interviews, focus group discussions, and case studies. The quantitative findings show that the quality of organizational communication has a negative and significant effect on resistance to change (β = -0.58; p < 0.001). In addition, aspects such as openness, consistency, timely delivery, participation, and empathetic communication are associated with mechanisms that reduce resistance by improving understanding, increasing trust, and strengthening employees' sense of ownership. The study also finds that an integrated communication strategy positively affects change effectiveness (β = 0.62; p < 0.001), and that communication effectiveness mediates the relationship between communication strategy and resistance reduction, supported by qualitative findings considering the importance of two-way communication, layered and repeated messaging, leveraging informal leaders, and management role modeling.